Two-Man Bobsled Push Start Analysis - Lopes, Alexandre Dias (J Hum Kinet, 2016)
The importance of push start times on bobsled performance was evidenced by some studies, but at this moment there is no article to the authors’ knowledge that describes the bobsled push start. Thus, the objectives of this study were to describe the two-man bobsled push start, analyze the differences between teams, and estimate the most important variable analyzed. We hypothesized that the pilot and brakeman athletes’ movement patterns during a bobsled pushing start can be described. The images used in this study were obtained during the men’s two-man XIV World Championship of Bobsled (2004). Fifteen best teams participating in the championship were recorded, and four start runs for each team were analyzed. The videos were captured by two digital video cameras. The pilot athletes were analyzed during the moment that they touched the lateral push bar of the sled, and the brakemen were analyzed during the first take-off and first landing. The teams were pooled in three groups of five teams using the final ranking of pushing time. We concluded that there was a distinct pattern movement for pilots and brakemen. The initial position of the majority of the pilots was localized slightly behind the bar. After touching the lateral bar, the pilots remained in a semi-squat position, pushing the sled forward in a pattern of marching movement. All brakemen used the board attached to the track as a support for both feet at the start. The brakeman gave the greatest contribution to break the inertia of the sled. There was no significant difference of movement between the three groups analyzed for the pilot and the brakeman.